Enola Holmes and the mark of the mongoose - Springer, Nancy (Springer, Nancy. Enola Holmes mystery, 2023)
"In May of 1890, Enola Holmes is finally fully on her own and, no longer hiding from her older brothers Sherlock and Mycroft, attending classes and occasionally pursuing her chosen profession as a scientific perditorian, a finder of lost things and people. Wolcott Balestier, the representative of an American book publisher, arrived in London on a singular mission--to contract with English authors for their latest works. When Balestier disappears on the streets of London one day, his great friend--Rudyard Kipling--bursts into Enola's office looking for help in finding him. Brash and unwilling to hire a young woman, instead he turns to Sherlock Holmes. Convinced that evil has befallen Balestier, at the hands of rival American publishers who pirate the works of English authors, he sets the elder Holmes on the trail. But Enola is not one to accept defeat, especially not to her brother, and sets off on her own--determined to learn the truth behind the disappearance of the young American. Can book publishing truly be so ruthless and deadly or can the missing man be rescued from his apparent fate and returned to his friends and loved ones? The redoubtable Enola is determined to do just that, even if it means working with her brother Sherlock!" --